2004
DOI: 10.1074/jbc.m406802200
|View full text |Cite
|
Sign up to set email alerts
|

Aurora-A Abrogation of p53 DNA Binding and Transactivation Activity by Phosphorylation of Serine 215

Abstract: The tumor suppressor p53 is important in the decision to either arrest cell cycle progression or induce apoptosis in response to a variety of stimuli. Cip/WAF1 and PTEN, were inhibited by Aurora-A in a Ser-215 phosphorylation-dependent manner (i.e. phosphomimic p53-S215D lost and nonphosphorylatable p53-S215A retained normal p53 function). As a result, Aurora-A overrides the apoptosis and cell cycle arrest induced by cisplatin and ␥-irradiation, respectively. However, the effect of Aurora-A on p53 DNA binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
269
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(279 citation statements)
references
References 32 publications
5
269
2
2
Order By: Relevance
“…In contrast, it was shown in cultured cells that overexpression of Aurora-A phosphorylates p53, leading to its degradation Liu et al, 2004). It is therefore proposed that expression of Aurora-A induces tumorigenesis through degradation of p53 Liu et al, 2004). Differing from these studies, we found that overexpression of Aurora-A in mammary epithelium of our MMTV-Aurora-A transgenice mice did not cause an obvious alteration in p53 protein levels, nor an increase in apoptosis.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In contrast, it was shown in cultured cells that overexpression of Aurora-A phosphorylates p53, leading to its degradation Liu et al, 2004). It is therefore proposed that expression of Aurora-A induces tumorigenesis through degradation of p53 Liu et al, 2004). Differing from these studies, we found that overexpression of Aurora-A in mammary epithelium of our MMTV-Aurora-A transgenice mice did not cause an obvious alteration in p53 protein levels, nor an increase in apoptosis.…”
Section: Discussioncontrasting
confidence: 85%
“…Zhang et al (2004) also reported that overexpression of Aurora-A in mammary epithelium induced an accumulation of p53 and p53-dependent apoptosis. In contrast, it was shown in cultured cells that overexpression of Aurora-A phosphorylates p53, leading to its degradation Liu et al, 2004). It is therefore proposed that expression of Aurora-A induces tumorigenesis through degradation of p53 Liu et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The p53 tumor suppressor was shown to be phosphorylated by Aurora A leading to destabilization and degradation of the p53 protein in a mechanism reminiscent of what we have observed for BimEL. 47,48 Similarly, Aurora A was shown to phosphorylate BRCA1 and promote G2/M cell cycle progression. 49 Thus, in addition to the wide range of substrates targeted by Aurora A regulating chromosome and spindle dynamics during mitosis, it can also phosphorylate and deactivate tumor-suppressor pathways including Bim.…”
Section: Discussionmentioning
confidence: 99%
“…Aurora, a subfamily of serine/threonine protein kinase, includes Aurora-A, Aurora-B and Aurora-C in vertebrates [5]. Increased attention has now been focused on Aurora-A kinase because of its amplification and overexpression in several types of human tumors, such as breast cancer [6], colorectal cancers [7] and pancreatic cancer [8].…”
Section: Introductionmentioning
confidence: 99%